Sistema informático para la gestión contable, para empresas comerciales, utilizando java entorno empresarial. - Gómez Remache, José Giovany (2014)
This project describes the creation of a custom web application with specific functions for Trading Company "SIMASIHU", which will improve the operation of organizational, economic and mainly accounting processes, which arise in the day-to-day work of the company. Through an initial interview with the Manager, Engineer Víctor Andrés Sisalima, we could receive different comments, according to his initial perception of the management and the procedure that is carried out in each activity, being the accounting the main issue, in which is based this project. The system comprises several linked modules presenting a lot of windows, options, ads, and controls in general that frame a friendly interface developed for the purpose of provide an adequate handling of data and records. In this web application you can see different services focused on solving difficulties and to systematize a lot of processes such as Billing purchase and sale of industrial safety supplies, Administration of customers, Products, suppliers, employees and user Roles, Creation of price quotations, Credits and payments. Besides, to encompass all the accounting process that the company required as the record of Bills, entries, openings, books, accounting statements, etc. This Automation enables to accomplish all the needs and contributes to the development of daily tasks that the company performs. The document is divided in different sections that run through step by step the design of the system. First is conceptualized using the Web applications today, then identify the benefits that provide the management in the Trading Company "SIMASIHU". In the succeeding section are the technologies that we applied to the development, such as JEE (Java Enterprise Edition) JSP (Java Server Pages), ICEfaces and other components that formed this work. The final sections have all diagrams related to agile development process of Iconix. Furthermore, testing proposals with data analysis, finally we offer conclusions and recommendations which were the result of this project managing to solve, the initial problems and thereby becoming a management tool essential for the company that opened the doors to us.